2007
DOI: 10.1634/stemcells.2006-0391
|View full text |Cite
|
Sign up to set email alerts
|

Cbfb Enhances the Osteogenic Differentiation of Both Human and Mouse Mesenchymal Stem Cells Induced by Cbfa-1 via Reducing Its Ubiquitination-Mediated Degradation

Abstract: Core-binding factors are a small family of heterodimeric transcription factors that play critical roles in development. Whereas Cbfa-1, one of the three ␣ subunits in the family, is essential for osteogenesis, Cbfb, the only ␤ subunit, forms heterodimers with different Cbfas to increase their DNA binding affinity by inducing conformational changes. Although defective bone formation was found in both Cbfa-1 and Cbfb knockout animals, the precise role of the latter in osteogenesis remains unclear. To dissect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…It has long been known that CBF␤ increases the Runx proteins' affinity for DNA, 88,89 and it was more recently shown that it protects them from ubiquitin-mediated proteolysis. 37,90 However, genetic data in both flies and worms hint at other functions. For example, overexpression of a Drosophila Runt protein that could bind DNA but not CBF␤ dominantly inhibited its wild-type counterpart, suggesting that it was occupying its DNA binding sites but forming nonfunctional complexes.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that CBF␤ increases the Runx proteins' affinity for DNA, 88,89 and it was more recently shown that it protects them from ubiquitin-mediated proteolysis. 37,90 However, genetic data in both flies and worms hint at other functions. For example, overexpression of a Drosophila Runt protein that could bind DNA but not CBF␤ dominantly inhibited its wild-type counterpart, suggesting that it was occupying its DNA binding sites but forming nonfunctional complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The WT Runx2 expression vector was described previously. (33) After being linearized by PmeI (New England Biolabs), the plasmids were transformed into BJ5183 cells, and successful recombination was verified by PacI (New England BioLabs) digestion. The vectors expressing His-tagged series of Runx2 were constructed as follows.…”
Section: Dna Constructionmentioning
confidence: 99%
“…Control IgG or anti-Runx antibodies were included as indicated. (41,42), in part by limiting their ubiquitin-mediated degradation (43,44) and by increasing the affinity of Runx proteins for DNA (45). Therefore, to determine whether any member of the Runx family is required for the expression of RANKL, we silenced Cbfb using shRNAs introduced via lentiviral transduction.…”
Section: Figure 3 Runx2 Is Not Required For Rankl Expression In Mefsmentioning
confidence: 99%